Congenital Syphilis as prenatal assistance factor in Campo Grande – MS - Figueiró-Filho, Ernesto Antonio; Gardenal, Renata VC; Assunção, Leandro A; Costa, Gabriel R; Periotto, Carlos Renato L; Vedovatte, Cássia A; Pozzobon, Leonardo R (Brazilian Journal of Sexually Transmitted Diseases, 2007)
Introduction: three point five percent of pregnant women with syphilis in Brazil, who represent the risk of vertical transmission of 50-85% and perintal mortality rate of 40% were estimated. Among the risk factors, the lack of regular prenatal assistance is punctuated. Objective: verifying congenital syphilis (CS) prevalence in Campo Grande and describing epidemiological, obstetrical and perinatal data of the studied population, highlighting its role as a marker of prenatal quality assistance. Methods: observational and transversal study of CS cases occurred in 512 post-partum women from February 1st to April 30th 2006. The diagnosis was based on Ministry of Health criteria. An interview during delivery hospitalization was made to obtain the data. Results: the CS coefficient found was 23.4/1.000 births. The CS rate was presumed according to the criteria of CDC. The neonatal coefficient was zero. Out of the pregnant women with syphilis, 75% informed regular prenatal assistance, 33% were correctly treated during prenatal period. Pregnant women’s partners were not treated in 60% of the cases. The children that the infected women already had were screened for syphilis only in 40% of the cases. Conclusion: the prevalence of CS observed was 2.3%. A high puerperal prevalence of syphilis infection, not adequate treatment of the women and their partners and inadequate screening of the children those women already had were observed. The exposed data enhance the prenatal importance in reducing the CS, emphasizing the best regular prenatal assistance to the studied population.